The Dynamics of Polygamy and Divorce in Muslim Countries - Madina, Dinda Difia; Meidina, Ahmad Rezy; Zein, Anwar (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
This article talks about the practice of Islamic family law in the Muslim world; Türkiye, Pakistan, and Indonesia which focus on polygamy and divorce. Talking about polygamy and divorce must be familiar to many people because polygamy is a very sensitive scourge when someone does that. Likewise, with divorce, this kind of thing becomes the subject of gossip in society when a family gets divorced. This paper will explain how family law is in the Muslim world, especially Turkey, Pakistan, and Indonesia with the main study of polygamy and divorce which aims to understand the understanding of society from all walks of life regarding the discussions between the two. This research is a literature study that focuses on discussing polygamy and divorce in three Muslim countries; Türkiye, Pakistan, and Indonesia. The data collection method in this study used documentation, namely collecting books, notes, and others that had relevance to the research, which were then analyzed. The results of this study are; (1) Turkey prohibits polygamy, which is contained in the book of the Ottoman Law of Family Rights, Pakistan also prohibits polygamy until written permission from the wife and the arbitral council, Indonesia legalizes polygamy referring to the Marriage Law. (2) Turkey in the event that a divorce ends with the finalization of a court decision and a waiting period of 300 days stipulated by the Turkish Civil Code, likewise Pakistan regulates divorce in two different rules, one using the Dissolution of Muslim Marriage and the other using Muslim Family Law Ordinance, divorce in Indonesia is regulated in Marriage Law Number 1 of 1974.